Penyuluhan Kesehatan Reproduksi Remaja Di Santiwit Songkhla Technological College Thailand: (Mahasiswa PAI Fakultas Ilmu Keislaman) - Alif Achadah; Annisa Chonitatin; Latifatus Sa’diyah (Lembaga Pengembangan Kinerja Dosen, 2024)
In the current era of development, globalization is something that almost all individuals cannot avoid. Globalization is an illustrative form of interaction between various individuals in certain types of fields. The emergence of globalization is due to the existence of modern-industrial civilization which is driven by the increase in western culture which has had quite a significant influence. The existence of globalization creates a very fast and unstoppable flow because various information comes from various corners of the world. There are many things that can result from globalization, both positive and negative. One of the negative impacts caused by the influence of globalization is promiscuity. So it is necessary to take preventive measures before this happens and harms many parties. Students from the Faculty of Islamic Sciences, Raden Rahmat Islamic University, Malang themselves chose to hold youth reproductive health outreach activities with the aim of helping and improving the condition of teenagers related to their reproductive health. So that it makes them aware and more diligent in caring for it. Health education carried out in Powocho school grounds or vocational high schools in Thailand itself begins with holding joint sports activities and continues with indoor counseling activities. This information activity on adolescent reproductive health is of great interest to students and it is hoped that it can be used as a lesson and make students more aware of the importance of their reproductive health and also more diligent in caring for and maintaining their health.